Perlindungan Hukum Terhadap Korban Cyber Crime di Indonesia dalam Aliran Hukum Pada Kasus Pencurian Data Pribadi - Idriansyah, Alfi Salsabilah; Afifah, Nur (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
With the rapid development of information and communication technology, various types of cybercrime, especially personal data theft, are becoming more possible. In today's digital era, legal protection for victims of personal data theft is an important issue. This article examines the legal protection provided to victims of personal data theft on the internet from the perspective of Indonesian law. This study uses qualitative methodology and literature study. The study shows that Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE) and Regulation of the Minister of Communication and Informatics Number 20 of 2016 concerning Protection of Personal Data in Electronic Systems are the main laws in Indonesia that regulate personal data protection. Victims have rights protected by this legal protection, such as the right to be notified in the event of a data leak, the right to compensation, and other rights. However, these regulations still need to be improved to accommodate rapid technological developments and provide legal certainty for all parties.